Role of farmers in the evaluation of an improved variety: The case of S35 sorghum in northern Cameroon - Kamuanga, M.; Fobasso, M. (1994)
Efforts to develop high-yielding, stable, early-maturing sorghum varieties in northern Cameroon produced an apparently resounding success with on-farm tests of the variety S35 from 1983-85. This caused great excitement and led to the recommendation of S35 to the regional extension agency in 1986. In subsequent years, under more favourable rainfall conditions, farmers reported serious agronomic problems with the variety. However, informal surveys revealed some farmer-initiated strategies for incorporating S35 into their traditional cropping systems. In 1990 an adoption survey to measure research impact revealed that 13% of farmers had adopted the new variety. Results of regression models suggest that farmers tend to adopt S35 more on its own merit than as part of a package of recommendations. Adoption rate is higher among farmers who planted improved sorghum three to five years ago, and location in drought-prone zones is determinant. Reasons for non-adoption, together with these results, now form the basis of revising breeding objectives in order to respond better to farmers' needs.